Numerical simulation study of vortex cavitation and induced pulsation characteristics in spiral lobe pumps - Hengzhi Zhou; Chun Xiang; Peijian Zhou; Yanzhao Wu; Long Meng; Liping Sun (AIP Advances)
Lobe pumps are used in many different sectors because of their versatility and effectiveness for managing multiphase flows. In this study, three-dimensional unsteady numerical simulations are performed to evaluate the vortex cavitation phenomenon in these pumps. The work combines dynamic meshing techniques, advanced vortex recognition methods, and a full cavitation model to provide insight into the genesis, evolution, and influence of vortex cavitation on pump performance. The results of the study demonstrate that under high-speed and high-pressure conditions, vortex flow occurs at the edge of the rear of the rotor lobe in the suction chamber of the lobe pump, resulting in the production of vortex cavitation. Cavitation is most strong at the core of the vortex, while the degree of cavitation at the edge of the vortex gradually diminished. The gas volume fraction reduces from 0.135 to 0.0832, and this makes the pressure decrease from 1.055 to 1.02 MP. The process of genesis, development, and removal of vortex cavitation is cyclic. At different levels of cavitation, the degree of pulsation in pump outlet flow, pressure, and radial force increases with increasing cavitation. Periodic vortex cavitation leads to periodic changes in pump output pressure, flow rate, radial force, and axial force.